A Theory of Indifference Based on Status-Seeking Behaviour - Sugata Marjit; Krishnendu Ghosh Dastidar; Abhilasha Pandey (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper explores the reluctance of men (women) to acknowledge or recognise the work, comments, and claims of new ideas by other men (women) via widespread and intense demonstrations of indifference. Instances like desk rejections by journals by not allowing papers to reach a review stage, deliberately ignoring responses to respectful and cordial emails, or not referring to relevant papers in references may be related to a kind of status-seeking behaviour beyond what is projected as the real reason for such actions. Against this backdrop, this paper draws from the contemporary experimental psychology and economic theory literature on the causes and consequences of status-seeking behaviour. It integrates the idea in a simple two-player non-cooperative game theoretic framework to explain why even in a world where "Recognition" is a socially optimal strategy, "Indifference" will persist at an equilibrium. We also look at the formation of self-pampering clusters in social media as a resistance to indifference.
Keywords: D91; C72; C73; 330; experimental psychology; status-seeking behaviour; indifference; recognition; non-cooperative games; repeated games